Hybrid Work System, Employee Productivity, Job Satisfaction, Journalists and Editors, Media Industry, KOMPAS Gramedia - Fauzia, Eva (Journals of Ners Community, 2024)
This study aims to analyze the form of legal protection for workers in the gig economy sector in the digital economy era, focusing on a comparative study between the European Union and Southeast Asia. The gig economy phenomenon that is growing rapidly through digital platforms such as online transportation services, freelance marketplaces, and food delivery services, presents new challenges related to the legal status of workers, social protection, and often unclear employment relationships. The research method used is normative legal research with a comparative approach. Data sources were obtained from international legal instruments, regulations in the European Union (e.g. EU Directive on Platform Work), regulations in several Southeast Asian countries, as well as academic literature and relevant court rulings. The analysis was carried out by examining the differences and similarities of legal norms, worker protection mechanisms, and the effectiveness of their implementation in each region. The results show that the European Union has been more progressive in formulating legal instruments that provide minimum protection for gig economy workers, such as access to social security, the right to transparent employment contracts, and protection against arbitrary termination. Meanwhile, in Southeast Asia, most regulations are still limited, with approaches that tend to place gig workers as independent partners, so the legal protections are relatively weak. In conclusion, there is a regulatory gap between the European Union and Southeast Asia in protecting gig economy workers. The implications of this study underscore the need for regional regulatory harmonization in Southeast Asia that adopts good practices from the European Union, so that the rights of digital workers can be protected without hindering economic innovation. This research also opens up opportunities for policymakers to formulate an adaptive legal framework that is able to balance the interests of workers, platform companies, and the state.